(untitled) - Ishikawa, Akira (New York, 1985)
The corrolary relationship between strategic budgeting and strategic planning is explored and explained in this major analysis of strategic budgeting, and strategic budgeting in specific companies is compared and evaluated qualitatively. The author then introduces an innovative procedure of strategic budgeting and describes how to adapt it to these organization-specific examples. The design and development of strategic budgeting systems are described in detail, with particular emphasis on information-intensive industries, such as aerospace, artificial intelligence and computers. The application of strategic budgeting techniques to small businesses and government (federal and local) is also covered. Critical comparisons are made between Japan and the U.S., and several sample Japanese cases are presented here for the first time.
Keywords: Budget in business,Business planning; Case studies,Case studies; Japan